GENDER IMPACTS FROM WEATHER EXTREMES IN SOUTH INDIA - Xenarios, Stefanos (Nazarbayev University Graduate School of Public Policy, 2021)
The current study suggests a gender differentiated impact framework for the assessment of climate variability effects on rural communities in South India.
Keywords: gender studies; UNFCCC; IPCC; NAPAs; South India; Research Subject Categories::SOCIAL SCIENCES; weather extremes impact; gender equality